Impact of Salinity on Infant and Neonatal Mortality in Bangladesh - Joseph, George (World Bank, Washington, DC, 2019)
In this paper, the impact of salinity on maternal and child health in Bangladesh is analyzed using data from the Bangladesh Demographic Health Surveys. A U-shaped association between drinking water salinity and infant and neonatal mortality is found, suggesting higher mortality when salinity is very low or high. With fresh drinking water, the marginal effect of salinity measured by groundwater electricity conductivity on infant death is always negative. With brackish drinking water and slightly saline water, the negative effect is small. As drinking water becomes moderately saline, the predicted probability of infant death starts to increase, and the marginal effect becomes and remains positive. The relationship between drinking water salinity and neonatal death shows a similar pattern. Finally, freshwater with very low concentration of healthy minerals and severely saline water with very high detrimental sodium can be harmful for infant and neonatal health during pregnancy. Severe salinity needs to be addressed if the recent gains in infant and neonatal mortality are to be sustained, especially in the coastal areas of Bangladesh.